Felicia's journey - Trevor, William 1928-2016 (Viking, 1995)
A psychological horror story in which a man helps women in distress, only to murder them. The story is told through the eyes of an Irish girl who escapes the fate that befell the others. The setting is Britain. By the author of Two Lives.
Keywords: Irish -- Travel -- England -- Midlands -- Fiction; Middle aged men -- England -- Midlands -- Fiction; Pregnant women -- England -- Midlands -- Fiction; Young women -- England -- Midlands -- Fiction; Midlands (England) -- Fiction; Fiktionale Darstellung; Psychological fiction